PEMBERDAYAAN BUMDES MESTHI MAKMUR DI DESA KERASWETAN KECAMATAN GENENG KABUPATEN NGAWI - Taufiq Yuli Purnama; Anik Tri Haryani; Meirza Aulia Chairani; Retno Istiwati (Universitas Merdeka Madiun, 2022)
— According to the Law of the Republic of Indonesia Number 6 of 2014 concerning Villages, Villages are legal community units that have territorial boundaries that are authorized to regulate and manage government affairs, the interests of local communities based on community initiatives, origin rights and traditional rights that are recognized and respected in the government system of the Unitary State of the Republic of Indonesia. According to Government Regulation Number 11 of 2021, Village Owned Enterprises or called BUMDes are legal entities established by villages and/or together with villages to manage businesses, utilize assets, develop investment and productivity, provide services, and/or provide types of businesses. others for the greatest welfare of the Village community. This community service activity aims to assist village officials and the community of Keraswetan Village, Geneng District, Ngawi Regency in making village economic programs (microeconomics) in utilizing village potential through BUMDes. The systematic implementation of community service activities uses legal and practical counseling methods to discuss problems related to the establishment of Village Owned Enterprises (BUMDes) that have been faced so far. The result of the implementation of service is the actualization of science and knowledge academically to the community, especially rural communities who need assistance. Together with village officials and village communities in exploring the potential of the village to be used as efforts economically for welfare so that the work program of the BUMDes in the Keraswetan Village is realized.